Advancing the practice of performance measurement in public organizations: Observations from the tennessee municipal benchmarking project. Issue 1 (1st March 2016) - Shults, Christopher
Abstract : David Farmer suggests that there are multiple ways of looking at social science concepts. No one perspective, or lens, is superior, but taken together, multiple lenses can be enriching and yield a clearer picture of complex ideas. The purpose of this paper is to illustrate Farmerʼs multiple lenses approach by looking at performance measurement in the public organizations that participate in the Tennessee Municipal Benchmarking Project (TMBP). Observations from the TMBP suggests that utilizing only one lens can be detrimental to the decision-making process, while employing multiple lenses acknowledges multiple factors in the decision-making process and aides decision makers in reaching a consensus.